"Digital Show-How": Extreme Active Learning for Introductory Programming - Stotts, David (International Conference on Computer Science & Education, 2019)
For the past ten years we have employed active learning methods in introductory programming classes at UNC Chapel Hill. In this report we present experience with one such method we call "digital show-how", in which students learn to program apprentice-fashion, by doing programming in class. Digital show-how is extreme active learning. Students do a lot of programming, in real-time, in class as the instructor shows them how. They get instant feedback on their work, and so have constant low-stakes assessments. We describe the goals for the classes, the tools and methods we have developed to support digital show-how, and the results we have measured on how well the goals are being met.